Study of Manufacture Company Strategy in Implementing ISO 9001:2015 & ISO 140001 - Muhammad Akrim, Zikri Habibie; Sidjabat, Filson Maratur (UNM Environmental Journals, 2019)
In early 1980’s environmental issues were increasing, several policies were made in countries as a concern to environment, even the government has the policy about environment. One of the standards used in company related to environment is ISO 14001.Beside environmental management system companies need to get an international confession stating that their products and systems are appropriate. The international standard related to the quality management that can be used is ISO 9001:2015.In this study author try to comparing manufacturing company such asPT. Apac Inti Corpora, Omron Manufacturing and LG Electronicstrategy in implementing the ISO 9001:2015 and ISO 14001:2015 certification.